Deep Learning in Biology: 3D Representation of Online and Reality - Suprapto, Purwati K.; Ardiansyah, Ryan; Chaidir, Diki M.; Baiq , Baiq; Meylani, Vita (Future Science / FSH-PH Publications, 2022)
Deep learning is required to examine biological material, particularly abstract content, either in the laboratory alone or with internet literature. This study aims to compare the effectiveness of learning through practicum versus learning through a combination of practicum (real-world data) and online literature review in terms of the ability to represent the three-dimensional (3D) model of plant tissue structure in a plant anatomy course. This study employed a quantitative approach with a quasi-experimental design in the posttest alone control group. This research used Purposive sampling to choose the research sample, which consisted of two classes of students enrolled in a plant anatomy course. ANOVA was used to analyze the data, with a significance level of 0.05. The results indicated a significant difference in learning when combined practicum was with online literature study visuospatial when practicum was used alone with a more excellent 3D model representation value in the class. Classes that combine an applied practicum with an online literature review have a grade point average of 73.61.